On the interaction of energetic electrons with a tearing mode in density-sweeping tokamak plasmas. (15th May 2015) - Li, Erzhong; Lin, S.; Shen, B.; Hu, L.
Abstract: We present a detailed study on the interaction between energetic electrons and the m / n = 2/1 tearing mode ( m, n are respectively the poloidal and toroidal mode number) which was investigated in a deliberate experiment via actively controlling the bulk electron density (Li et al 2014 Nucl. Fusion 54 042001). Energetic electrons were generated by the residual loop voltage in the ohmically heated plasma where periodic bursts of magnetic perturbations were frequently observed. The frequency evolution of the mode is similar to the well-known fishbone ( m / n = 1/1) or the 'off-axis' fishbone in high-beta plasma (Heidbrink et al 2011 Plasma Phys. Control. Fusion 53 085028), but demonstrates the characteristic of a tearing mode. In particular, it can increase the average intensity of H-alpha radiation as the mode grows, which is distinctive from the following oscillatory phase. The dynamics of the mode are strongly influenced by the increasing background electron density, suggesting a collisionality dependence. This qualitatively agrees with the prediction of a drift kinetic theory.